A review on software defined network security risks and challenges - Tsehay Admassu Assegie; Pramod Sekharan Nair (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Software defined network is an emerging networking architecture that separates the traditional integrated control logic and data forwarding functionality into different planes, namely the control plane and data forwarding plane. The data plane does and end to end data delivery. And the control plane does the actual network traffic forwarding and routing between different network segments. In software defined network the networking infrastructure layer where the entire networking device, such as switches and routers reside is connected with the separate controller layer with the help of standard called OpenFlow protocol. It is a standard protocol that allows different vendor devices like juniper switches, cisco switches and huawei switches to be connected to the controller. The centralization of the SDN controller made the network more flexible, manageable and dynamic, such as provisioning of bandwidth, dynamic scale out and scale in compared to the traditional communication network, however the centralized SDN controller is more vulnerable to security risk factors such as DDOS and flow rule poisoning attack. In this paper we will explore the architectures and principles of software defined network and security risks with the centralized SDN controller and possible ways to mitigate these risks.